PELATIHAN DESAIN CERDAS CANVA PETA GRAFIS DI DESA SINDANGMULYA - Sya'bani, Zalfaa’ Zain; Pujihastuti, Isti; Irham, Irham (An-Nizam, 2024)
Technological advancements play a crucial role in supporting the growth and development of a nation, including in spatial planning. However, the lack of public understanding of modern design technology poses a challenge in creating effective regional maps, particularly in Sindangmulya Village, Bekasi. To address this issue, a Canva-based graphic design training program was conducted to enhance community skills in designing functional and visually appealing maps. This training adopted a participatory approach that combined theoretical knowledge with practical application, enabling participants to understand fundamental graphic design principles and apply them directly in village mapping. The participants consisted of Sindangmulya Village residents involved in regional planning and management. The effectiveness of the training was evaluated through a questionnaire assessing participants’ improvement in using Canva for map creation to support navigation and infrastructure planning. The results indicated a significant enhancement in participants’ competencies, both in terms of conceptual understanding of design and technical proficiency in using Canva. This training is expected to empower the community to contribute more independently and effectively to village spatial management. In conclusion, the Canva-based graphic design training has proven to be an effective solution for enhancing community skills in village map creation, thereby supporting better village development and planning.